Exploring Digital Literacy Strategies for Students with Special Educational Needs in the Digital Age. - et. al., Abdul Jalil Toha Tohara, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
21st century learning requires students to be equipped with learning skills, knowledge, media literacy and also life skills. In order to achieve these skills, the school curriculum embeds the use of technological tools and strategies to provide teaching and learning strategies for learners, including students with special needs or Special Needs Students (SNS). Studies found that students struggle to cope with their studies in the digital learning environment due to their limited digital literacy skills. Digital Literacy skills are essential to develop as independent learners in the digital age. Previous studies have shown that digital literacy skills have demonstrated a positive influence on student performance. However, limited studies have been conducted on the issue. This paper aims to discuss the concept of digital literacy skills to support teaching and learning strategies for SNS in Malaysia from teachers’ perspectives. The digital literacy skills model consists of cognitive skills, technology and ethics as basic guidelines to explore digital literacy teaching and learning strategies for SNS. This concept has been tested as a preliminary study in a course by interview with five teachers who taught a Desktop Publishing among SNS. From the findings, it was shown that the digital literacy skills model is able to improve the teaching and learning strategies needed for SNS in the digital environment.